Teaching Vocabulary Through Song At The Second Semester Of The Seventh Grade Students - savia indri kurniasari (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2022)
Vocabulary is one of the important elements, because vocabulary is the base element for producing language in order to communicate. The purpose of this research is to teach vocabulary through song in the second semester of the seventh grade at SMPN 1 Kauman during the academic year 2020/2021. In this research, the researcher used qualitative descriptive research method.The objective of this research are to describe the process of teaching vocabulary by using song and students problems in the process of learning vocabulary by using song. The result of this research shown that most of problems that faced by students are memorizing word, but when media to teach vocabulary using song they were more interested to learn vocabulary